Effect of different tillage systems in some soil physical properties, operation costs of machines and yield of wheat crop - Melli, ‏​‏​‏​​‏​‏​​‏​‏​‏​‏​‏​‏ Ali (Arab Journal for Sciences and Research Publishing, 2016)
The study was conducted in Al-Hasakah governorate to study some of the physical properties of the soil: moisture content, virtual density, dry density, total soil porosity, air porosity, vacancy rate, yield of wheat yield and total costs. The experiment parameters were as follow T1: T2 plow: Plowing and planting together with a planting machine (T3): Planking plow (T4): Disc comb (common system). These were compared with T0 (untreated soil) . The total density, the percentage of voids, the air porosity, the dry and dry density of the soil and the moisture content at T4 decreased, and the yield was higher at T3 and the lowest was at (T3) T4). (T / T> T1> T3), and the unit (LS / kg) had the following ascending form: T1> T2> T4> T3 .